2018
DOI: 10.1186/s12937-018-0322-5
|View full text |Cite
|
Sign up to set email alerts
|

Early feeding of larger volumes of formula milk is associated with greater body weight or overweight in later infancy

Abstract: BackgroundThe relation between infant feeding and growth has been extensively evaluated, but studies examining the volume of formula milk consumption on infant growth are limited. This study aimed to examine the effects of early feeding of larger volumes of formula on growth and risk of overweight in later infancy.MethodsIn total, 1093 infants were studied prospectively. Milk records collected at 3 mo of age were used to define the following 3 feeding groups: breast milk feeding (BM, no formula), lower-volume … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 34 publications
1
34
1
2
Order By: Relevance
“…We were not able to capture the quantity consumed or the regularity of milk consumption. Both could mediate the effect on child growth 25,26 . In addition, a 24 hour recall is not the optimal method to measure feeding practices and there is variability in daily feeding practices 18 .…”
Section: Discussionmentioning
confidence: 99%
“…We were not able to capture the quantity consumed or the regularity of milk consumption. Both could mediate the effect on child growth 25,26 . In addition, a 24 hour recall is not the optimal method to measure feeding practices and there is variability in daily feeding practices 18 .…”
Section: Discussionmentioning
confidence: 99%
“…This is the first study to show that formula intake increases the odds of slow weight gain compared to breastfeeding, although it was not associated with weight status at four months. Most prospective studies have found a positive association between formula feeding and rapid weight gain [13,14,15,33,34,35,36,37], showing a different pattern of weight gain by type of feeding. For example, the Darling study following 87 infants (46 breastfed and 41 formula fed) for 12 months showed similar WHL z-scores between breastfed and formula fed infants during the first four months, but then from the 5th to 18th month, WHL z-score was consistently higher among formula fed infants [35].…”
Section: Discussionmentioning
confidence: 99%
“…An analysis of 70,000 infants enrolled in the WIC Program found that obesity at age 4 was higher in infants fed only formula (25.9%) compared to those exclusively breastfed (19.8%) [12]. Additionally, very recent longitudinal studies have shown that infants fed formula during the first 3 months of life gain significantly more weight compared to breastfed infants at six or nine months of age [13,14,15]. Formula overfeeding (feeding above recommended guidelines by age) appears to also influence weight, since bottle-fed infants have less control over feeding volumes [16].…”
Section: Introductionmentioning
confidence: 99%
“…where Fi is the milk consumption of the applicable consumption rates of milk (kg/day), which was chosen based on the data of consumption supplied by WHO [30]. It was found that the consumption of milk for children that are 1-3 years old (14 kg), 4-6 years old (21 kg) and 7-10 years old (32 kg) was nearly 750, 483 and 500 mL/day, respectively [31,32]. The Ci (concentration of BaP), ∑7PAHs and ∑13PAHs are summarized in Table 5.…”
Section: Edi Expressed In Mg/daymentioning
confidence: 99%